FAKTOR-FAKTOR YANG MENYUMBANG KEPADA KEBERKESANAN PENGAMALAN 5S DI ORGANISASI - Ardhana, Ahmad (Universiti Malaysia Sarawak (UNIMAS), 2004)
The purpose of this study is to determine the factors that contribute to the effectiveness of 5S practices in Toko Electronic (Sarawak) Sdn. Bhd. The factors identified were demographical factors that are education level and services period. Meanwhile, organization factors are top management commitment factor, training factor, group co-operation factor, motivation factor, reward factor and internal audit factor. Further, this study also aimed to find out the level of effectiveness of 5S in Toko Electronic. A total of 64 respondents from 2277 workers, at Toko Electronic were involved in this study. Data analyzed by using Statistical Packages for Social Science (SPSS) version 11.0. In this study, the descriptive statistical method was used to analyze the frequency and the percentage of respondent in demographical factor. Meanwhile, the inference statistical method using Pearson Correlation Test to find out the correlation between the factors of the study with the effectiveness of 5S practice and the One- Way ANO VA Test was used to find out the different between factors and the effectiveness of the 5S practice. The findings show at high level of the effectiveness of 5S in Toko Electronic at high level at 100 %. The One-Way ANOVA Test shows there is no significant difference between demographical factor and the effectiveness of 5S practices whereby, F= 0.517, p= 0.559 > 0.05 and F=2.691, p=0.077 >0.05. The findings of the Pearson Correlation Test shows the result of top management commitment factor (r= 0.461**, p=0.000<0.01), training factor (r= 0.276*, p=0.043<0.05), group co-operation factor (r= 0.689**, p=0.000<0.01), motivation factor (r= 0.448**, p=0.001 <0.01) and internal audit factor (r= 0.622* *, p=0.000<0.01). This result show that these factors correlate with the effectiveness of 5S practice. The factors that does not correlate with this study is the reward factor with findings r= 0.232 and p=0.092